Specific echocardiographic findings useful for the diagnosis of common pulmonary vein atresia - Hiroyuki Nagasawa (Pediatric Reports, 2015)
In this paper, we report a case of common pulmonary vein atresia, which is a very rare disease characterized by cyanosis, heart failure and pulmonary hypertension. Reverse flow in the pulmonary artery at end-diastole as well as in the isthmus of the aorta from early systole to end-diastole detected by echocardiography were found to be specific features useful in diagnosing the disease.